The new rules of marketing & PR - Scott, David Meerman (John Wiley & Sons, Inc., 2013)
The benchmark guide to marketing and PR, updated with the latest social media and marketing trends, tools, and real-world examples of success The New Rules of Marketing & PR, 4th Edition is the pioneering guide to the future of marketing, an international bestseller with more than 300,000 copies sold in over 25 languages.